Finite Verb Forms in Nubri With a Focus on Conjunct-Disjunct Distinction - Dhakal, Dubi Nanda (Nepalese Linguistics, 2022)
This paper is a preliminary report on the finite verb forms in Nubri. Nubri reveals the verb agreement pattern known as 'conjunct-disjunct (C-D) like some Tibetan varieties, such as Kyirong Tibetan, Gyalsumdo among others. Nubri shows fairly consistent pattern of the verbs in the past tense marked with -hin, and –soŋ for conjunct and disjunct respectively. However, this is not consistent in the non-past tense.